EGFR mutant allelic-specific imbalance assessment in routine samples of non-small cell lung cancer. Issue 9 (5th June 2015) - Malapelle, Umberto; Vatrano, Simona; Russo, Stefania; Bellevicine, Claudio; de Luca, Caterina; Sgariglia, Roberta; Rocco, Danilo; de Pietro, Livia; Riccardi, Fernando; Gobbini, Elisa; Righi, Luisella; Troncone, Giancarlo
Abstract : In non-small cell lung cancer (NSCLC), the epidermal growth factor receptor (EGFR) gene may undergo both mutations and copy number gains. EGFR mutant allele-specific imbalance (MASI) occurs when the ratio of mutant-to-wild-type alleles increases significantly. In this study, by using a previously validated microfluidic-chip-based technology, EGFR-MASI occurred in 25/67 mutant cases (37%), being more frequently associated with EGFR exon 19 deletions (p=0.033). In a subset of 49 treated patients, we assessed whether MASI is a modifier of anti-EGFR treatment benefit. The difference in progression-free survival and overall survival between EGFR-MASI-positive and EGFR-MASI-negative groups of patients did not show a statistical significance. In conclusion, EGFR-MASI is a significant event in NSCLC, specifically associated with EGFR exon 19 deletions. However, EGFR-MASI does not seem to play a role in predicting the response to first-generation EGFR small molecules inhibitors.